Effectiveness of lateral femoral cutaneous and femoral nerve block in managing postoperative pain for hemiarthroplasty patients - Kazi Mahzabin Arin; Shofina Sultana; Ayesha Sultana; Abdul Hannan Mohammad; Chandra Shekhar Karmakar; AKM Akhtaruzzaman (Bangabandhu Sheikh Mujib Medical University Journal)
Background: The fascia iliaca compartment block is commonly used for postoperative analgesia after hemiarthroplasty. However, the method often fails to adequately manage pain due to frequent sparing of the lateral femoral cutaneous nerve. This randomised controlled study was conducted to compare the efficacy of lateral femoral cutaneous and femoral nerve blocks compared to fascia iliaca compartment block for postoperative pain management following hemiarthroplasty.